(68)Ga-Chloride PET Reveals Human Pancreatic Adenocarcinoma Xenografts in Rats—Comparison with FDG - Ujula, Tiina (Springer-Verlag, 2009)
PURPOSE: The aim of the study was to compare (68)Ga-chloride with 2-[(18)F]fluoro-2-deoxy-d-glucose (FDG) for the imaging of pancreatic xenografts. PROCEDURES: Rats with subcutaneous human pancreatic adenocarcinoma xenografts were evaluated in vivo by dynamic positron emission tomography (PET) and ex vivo by measuring radioactivity of excised tissues and by digital autoradiography of tumor cryosections. RESULTS: Both tracers were capable of delineating all subcutaneous tumors from surrounding tissues by PET. The standardized uptake values of tumors by PET were 0.9 ± 0.3 (mean ± SD) for (68)Ga-chloride (n = 13) and 1.8 ± 1.2 for FDG (n = 11). Ex vivo studies showed tumor-to-muscle ratio of 4.0 ± 0.3 for (68)Ga-chloride (n = 4) and 7.9 ± 3.2 for FDG (n = 4). CONCLUSIONS: (68)Ga-chloride delineated subcutaneously implanted pancreatic adenocarcinoma xenografts by PET, but the uptake was lower than FDG. Further studies to clarify the value of (68)Ga-chloride for PET imaging of tumors are warranted.